1993
DOI: 10.1557/jmr.1993.2404
|View full text |Cite
|
Sign up to set email alerts
|

Formation of V2O5-based mixed oxides in flames

Abstract: V2O5-TiO2 and V2O5-AI2O3 mixed oxide powders were synthesized in a hydrogen-oxygen flame using VOCI3, TiCl 4 , and A1(CH 3 ) 3 as precursors. The particle formation processes were investigated as a function of VOCI3 concentration by laser light-scattering and by collecting particles directly onto transmission electron microscopy grids. In the V2Os-TiO2 system, the oxides condense as an intimate mixture at all three VOCI3 concentrations. Spherical particles, 40 to 70 nm in diameter, are obtained. In the V2O5-AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…This catalyst is typically prepared in liquid phase processes. Nevertheless, Katz and co-workers [9,71,72] produced titania nanoparticles in a counterflow diffusion flame with 14, 25, and 50 wt% vanadia from TiCl 4 and VOCl 3 , however, they did not report the activity of their product. Stark et al [18] synthesized spherical titania particles coated homogeneously with amorphous vanadia in a co-flow diffusion flame from titanium tetraisopropoxide and vanadium oxotriisopropoxide.…”
Section: Vanadia Coated Titania Nanoparticles For Selective Catalyticmentioning
confidence: 99%
“…This catalyst is typically prepared in liquid phase processes. Nevertheless, Katz and co-workers [9,71,72] produced titania nanoparticles in a counterflow diffusion flame with 14, 25, and 50 wt% vanadia from TiCl 4 and VOCl 3 , however, they did not report the activity of their product. Stark et al [18] synthesized spherical titania particles coated homogeneously with amorphous vanadia in a co-flow diffusion flame from titanium tetraisopropoxide and vanadium oxotriisopropoxide.…”
Section: Vanadia Coated Titania Nanoparticles For Selective Catalyticmentioning
confidence: 99%
“…[23][24][25] In the present work, the V 2 O 5 -TiO 2 catalyst mixtures were prepared by drying oxide slurries, which were electrostatically stabilized by varying the suspension pH.…”
Section: Preparation Of the Catalyst Powder Mixturesmentioning
confidence: 99%
“…These lengthy procedures result in long are related to the ability of the (100) plane to accommodate processing times and often generate environmentally troublesome side streams. In earlier papers, we showed that one can produce mixed oxides with well-defined morpholo-gies in a single-step operation by flame synthesis using a nique for producing mixed oxides in a single step process counterflow diffusion flame burner (10)(11)(12). Most recently, has been described in detail elsewhere (10,12,14).…”
Section: Introductionmentioning
confidence: 99%
“…In earlier papers, we showed that one can produce mixed oxides with well-defined morpholo-gies in a single-step operation by flame synthesis using a nique for producing mixed oxides in a single step process counterflow diffusion flame burner (10)(11)(12). Most recently, has been described in detail elsewhere (10,12,14). Therewe applied this new high-temperature synthesis technique fore, the experimental setup and the procedure used for to produce vanadium-phosphorus mixed oxide catalysts forming and collecting the powders are reviewed here (13).…”
Section: Introductionmentioning
confidence: 99%